(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Everyone knows that calcium is very useful for tooth enamel. Therefore, we have been told about the benefits of milk since childhood. You need to know in which products and in what amount this important trace element is contained for the body.